СУБ’ЄКТ ДОБРОВІЛЬНОГО ВІДШКОДУВАННЯ ЗАВДАНОГО ЗБИТКУ АБО УСУНЕННЯ ЗАПОДІЯНОЇ ШКОДИ ЗА КК УКРАЇНИ - Бурбела, Юрій Сергійович (SUPREMANCE OF LAW, 2017)
The article is devoted to the actual problems of the subject of voluntary compensation for the damage or elimination of the harm caused to the Criminal Code of Ukraine. The peculiarities of voluntary compensation for the damage caused or the elimination of the harm caused to other subjects, except theperpetrator, are revealed. Scientific-substantiated recommendations for taking this fact into account in determining the limits or size of criminal legal incentives are formulated.